Historic house museums in the United States and the United Kingdom : a history - Young, Linda, 1953 June 16- (Rowman & Littlefield, 2017)
"This book addresses the phenomenon of historic houses as a distinct species of museum. By analyzing the motivation of the founders, and subsequent keepers, of house museums, the author identifies a typology that casts light on what they were intended to represent and their significance (or lack of it) today."--Provided by publisher